Influence of the North Pacific Victoria Mode on the Madden–Julian Oscillation - Wen, Tao; Chen, Quanliang; Li, Jianping; Ding, Ruiqiang; Tseng, Yu-heng; Hou, Zhaolu; Li, Xumin (Frontiers in Earth Science, 2020)
Using the observational data and the Coupled Model Intercomparison Project phase 5 (CMIP5) models this study examined the influence of the North Pacific Victoria mode (VM) on the Madden–Julian Oscillation (MJO). The results show that the February–April VM had a significant influence on the development and propagation of the MJO over the equatorial central-western Pacific (ECWP) during spring (March-May) between 1979 and 2017. Specifically, MJO development was favored more by positive VM events than negative VM events. These complicated connections could have been caused by the SST gradient anomalies associated with positive VM events, enhancing the convergence of low-level over the ECWP. When this is combined with warm SST anomalies in the equatorial central Pacific it could have led to a boost in the Kelvin wave anomalies, resulting in enhanced MJO activity over the ECWP. These conclusions indicate that the VM is an important factor in MJO diversity.